Identification of total productive maintenance barriers in Indian manufacturing industries. (2022) - Rathi, Rajeev; Singh, Mahipal; Sabique, Mohammed; Al Amin, Mohammad; Saha, Sujit; Hari Krishnaa, Molleti
Abstract: Every manufacturing industry are much concerned with their maintenance strategies adopted on the shop-floor to avoid breakdowns. As breakdowns directly leads to lowering the capacity utilization thus results in poor productivity. Recently, Total Productive Maintenance has emerged as one of the robust maintenance strategies and many big industries has adopted it in their work culture. Still, Indian manufacturing sector is not much familiar with the sustainable benefits of TPM and also hesitant to deploy TPM across their unit. In past, many manufacturing units has tried TPM but they are failing due to lack of knowledge base available on the barriers related to its successful implementation. The main goal of this study is to find key barriers related to TPM implementation across Indian manufacturing. A vast literature has been explored and potential barriers have been extracted that hinders the TPM performance in Indian context. Further, importance index has been compute based on expert opinion to find out most significant barriers of TPM implementation. Present results will provide the manufacturing managers the prominent barriers that can be tackled at early stage and will lead to successful execution of TPM across the unit.